2016
DOI: 10.3409/fb64_1.3
|View full text |Cite
|
Sign up to set email alerts
|

n-3 and n-6 Fatty Acid Changes in the Erythrocyte Membranes of Patients with <I>Clostridium difficile</I> Infection

Abstract: and n-6 fatty acid changes in the erythrocyte membranes of patients with Clostridium difficile infection. Folia Biologica (Kraków) 64: 3-10. The implications of circulating essential fatty acids (FA) on the inflammatory risk profile and clinical outcome are still unclear. In order to gain a deeper understanding of the role of polyunsaturated fatty acids (PUFA) in the pathogenesis of acute infection, we analyzed the FA content in red blood cell (RBC) membranes of patients with Clostridium difficile infection (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Typically, n-6 is thought to have pro-inflammatory effects. 73 In our study, a positive correlation was found between DII score and the proportion of erythrocyte membrane n-6 in OB group, after adjustment for model 2 ( P <0.05). The pro-inflammatory effect of n-6 is mainly related to C20:4 n-6.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Typically, n-6 is thought to have pro-inflammatory effects. 73 In our study, a positive correlation was found between DII score and the proportion of erythrocyte membrane n-6 in OB group, after adjustment for model 2 ( P <0.05). The pro-inflammatory effect of n-6 is mainly related to C20:4 n-6.…”
Section: Discussionsupporting
confidence: 50%
“…Competitive metabolism exists between n-3 and n-6 polyunsaturated fatty acids, whereas n-3 is generally considered to have anti-inflammatory effects, and a higher n-6/n-3 ratio in the diet is related to inflammation and multiple chronic diseases. 73,75 Our study found that DII scores were positively correlated with the proportion of the ratio of n-6 and n-3 of the erythrocyte membranes in OB group regardless of the adjusted models (P<0.05).…”
Section: Discussionmentioning
confidence: 62%
“…So far, the role of FA and their derivatives in the course of infection has been demonstrated (Shaikh and Edidin 2008 ; Tiesset et al 2009 ; Czepiel et al 2016 ), but there are no studies assessing this effect during neuroinfection. Moreover, the concentration of FA and ECB in neuroinfections was never directly assessed in the material taken from the CNS.…”
Section: Introductionmentioning
confidence: 99%